1998
DOI: 10.1016/s0006-3495(98)74071-8
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Activates Glycolysis of Goat Epididymal Spermatozoa: An NMR Study

Abstract: The present study explores the mechanism underlying the action of L-arginine on the metabolic activity of spermatozoa. Goat epididymal spermatozoa were incubated with different concentrations of L-arginine to determine its effect on the utilization of glucose, fructose, and pyruvate. NMR techniques have been applied to elucidate the effect of L-arginine, L-lysine, and L-ornithine on the glycolysis of epididymal goat spermatozoa. Whereas 31P NMR has been used to estimate the change of pH in the presence of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 22 publications
3
44
0
Order By: Relevance
“…3). In goat a high content of free amino acids was found in the ejaculate and the epididymal fluid, where these molecules could serve as chelating agents, in particular for toxic metals, and/or as oxidizable substrates for spermatozoa (Patel et al, 1998(Patel et al, , 1999. Amino acids could also serve as endogenous substrates in human sperm cells, but further studies are needed to validate this assumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). In goat a high content of free amino acids was found in the ejaculate and the epididymal fluid, where these molecules could serve as chelating agents, in particular for toxic metals, and/or as oxidizable substrates for spermatozoa (Patel et al, 1998(Patel et al, , 1999. Amino acids could also serve as endogenous substrates in human sperm cells, but further studies are needed to validate this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic studies have been performed in sperm cells from different species, such as goat (Patel et al, 1998(Patel et al, , 1999, boar (Jones & Bubb, 2000;Marin et al, 2003), turbot (Dreanno et al, 2000) and rhesus macaque Lin et al, 2009). Rat testicular tissue (Griffin et al, 2000) and human seminal plasma have also been subjected to metabolomic analyses (Hamamah et al, 1993;Gupta et al, 2011aGupta et al, ,b, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules act as chelating agents (especially of toxic metals), serve as oxidizable substrates for spermatozoa, provide buffers with protective influence on sperm cells, and undergo further metabolic changes in semen under the influence of transaminases and deaminases. Our results indicating the presence of arginine in goat cauda EF are highly implicated in its effect, in particular, stimulation of mammalian sperm motility in vitro (27)(28)(29), and in its beneficial effect on the sperm count for oligospermic semen after massive oral doses (30,31).…”
Section: Discussionmentioning
confidence: 82%
“…Administration of L-arginine to oligospermic and asthenospermic patients results in an improvement in both the sperm count and motility without any side effects (Scibona et al, 1994;Aydin et al;. L-arginine plays an important role in stimulating sperm motility in humans, rabbits, and goats under in vitro conditions (Aydin et al, 1995;Patel et al, 1998;Srivastava et al, 2006). It has been confirmed that L-arginine enhances the rate of glycolysis, resulting in higher rates of adenosine triphosphate and lactate generation in spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that L-arginine enhances the rate of glycolysis, resulting in higher rates of adenosine triphosphate and lactate generation in spermatozoa. The influence of arginine in reversing impairment caused by glycolytic inhibitors (potential contraceptives) has also been studied (Patel et al, 1998(Patel et al, , 1999. NO promotes mouse sperm capacitation and acrosome reaction (Griveau et al, 1995).…”
Section: Introductionmentioning
confidence: 99%